Suitability of barnyard millet (Echinochloa frumentacea)for development of low glycemic index and hypolipidemic pizza base - R Shrestha; S Srivastavaa
The present study was conducted to formulate low glycemic index pizza base using barnyard millet flour (BMF), analyze its nutrient composition and to evaluate its effect on the lipid profile of rats induced with hyperlipidemia. BMF pizza base was prepared by substituting refined wheat flour (RWF) with 40% of BMF. Incorporation of BMF resulted in significantly (p<0.05) higher crude fibre, protein, total ash, total dietary fiber (TDF), antioxidant activity, zinc and iron content in the pizza base in comparison to RWF pizza base. BMF incorporated pizza base with 8.89% of TDF was found to be rich in fiber. To determine the glycemic response and GI, ten non-diabetic adult female participants were administered with of BMF pizza base and pizza on alternate days. BMF pizza base and pizza with GI values of 36.67 and 43.43, respectively were observed as low GI products (<55). In order to analyze the effect of BMF pizza base on the lipid profile, albino rats (induced with hyperlipidemia) were supplemented with BMF pizza base diet for 28 days.Administration of BMF pizza base diet significantly (p<0.05) reduced triglyceride level, total cholesterol, very-low-density lipoprotein (VLDL), low-density lipoprotein (LDL) and increased high-density lipoprotein (HDL) level among hyperlipidemic rats. These results validate that the replacement of RWF with 40% of BMF is feasible for the formulation of low GI pizza base which also confers hypolipidemic property